Healthy Nutrition for Corona Virus Patients with Chronic Diseases: A Nutritional Interview in Tobruk, Libya - Amal R. Agila (African Journal of Advanced Pure and Applied Sciences, 2023)
This study is to know the association between chronic diseases and infection by corona virus in adults with chronic diseases and to explain healthy nutrition for solving COVID-19 outbreak crisis in Tobruk city. 240 cases (130 females and 110 males) aged (30-80) years were collected from Al-Hayat Center, Tobruk, Libya. All corona virus patients were diagnosed with chronic diseases including hypertension, diabetes mellitus, cardiovascular and kidney diseases. The nutritional questionnaire study was performed from 1 April to 30 November 2020. The questions were presented to the patient’s closely relatives due to the inability to communicate with them because of their serious health conditions. 7.1 % of patients were less than 30 years old whereas, 23.2% were older than 70 years old. This provides a suggestion that chronic diseases increase susceptibility to the corona virus. Also corona infection increases with age. Among 240 cases, 36 (15%) patients infected with corona virus were died. About 19 (8%) were males and 17 (7%) were females. There was no significant statistically difference (P = 0.355) between died males and females from corona infection. Among interviewed corona virus patients, there were patients diagnosed with hypertension (51%) and diabetes mellitus (36%) followed by cardiovascular diseases (9%) and kidney diseases (4%). There was no significant statistically difference (P = 0.319) between patients and their chronic sickness. Men are less interested in healthy nutrition than women and all men smoke. All patients drink at least 1 liter of water daily and did not make exercises and sleep irregularly.